MEDIA PEMBELAJARAN BERBASIS WEBSITE UNTUK SISWA PEDALAMAN BERORIENTASI LAUT - Rayuna Handawati; Lyzia Nabilla; Lisbet Gaite; Rantian Virta Eka Pratiwi; Rifni Aulia Safitri; Salwaa Aulia Firdaus; Yohanna Yohanna (Geography Education Study Program, Universitas Samudra, 2023)
This study aims to develop a product prototype that connects inland students who are always oriented or connected to the sea. Indonesia has aspirations to become a maritime country but currently people who are in the upstream area or far from the sea have not made rivers and seas as their main areas This research is expected to be useful for building the maritime paradigm of the Indonesian people, especially students who are far from the sea area through a prototype product. The products developed contain maritime materials and content such as history, culture, maritime resources, and maritime socioeconomics. The research method used in this study is descriptive qualitative using instruments from questionnaires by examining data. The results of this study show that most inland students have not mastered maritime material or content so a product is needed to always be able to connect with the sea. On the basis of this problem, a maritime website was developed that can be accessed by the public to build a maritime paradigm.